Tawakkul Mediates Between Personality Traits, Depression, and Anxiety in Pakistani Muslim Adults - Gondal, Muhammad Usama (Journal of religion and health, 2024)
Tawakkul in Islam is defined as the belief in the sufficiency of Allah (God) that invokes patience and efforts to achieve goals while accepting the outcomes unconditionally. The present research intended to investigate the mediating role of tawakkul between personality traits and mental health (anxiety and depression) in a purposive sample of (N = 350) Muslim adults. Urdu versions of three instruments, namely the Tawakkul Scale (Gondal, et al., 2021), Depression, Anxiety Stress Scale of (DASS 21; Aslam, 2018), and Neuroticism-Extraversion-Openness Five-Factor Inventory (NEO-FFI; Chishti & Kamal, 2002), were used to measure the variables. Path analysis revealed that extraversion had no association with tawakkul and anxiety, but it was inversely related to depression. Neuroticism was inversely related to tawakkul and positively related to both depression and anxiety, and these relationships were partially mediated by a low degree of tawakkul. Implications of the study and recommendations for future research are discussed.